Impact of Joint Laxity on 2-Year KOOS Outcomes of Posterior Stabilized Total Knee Arthroplasty - Randall, Amber L.; Wakelin, Edgar A.; Kah, James; Keggi, John M.; Koenig, Jan A.; DeClaire, Jeffrey H.; Ponder, Corey E.; Lawrence, Jeffrey M.; Plaskos, Christopher (The Journal of Knee Surgery, 2024)
The objective of this study was to determine relationships between intraoperative posterior cruciate ligament (PCL) sacrificing posterior stabilized (PS) total knee arthroplasty (TKA) laxity measurements throughout flexion and patient outcomes at 2 years post-TKA and to define clinically relevant laxity thresholds to optimize patient outcomes.In a single-surgeon study, PCL sacrificing TKA using a robotics-assisted platform with a digital joint tensioning device was performed in 115 knees in 115 patients. Final intraoperative joint laxity was recorded, and 2-year Knee Injury and Osteoarthritis Outcome Scores (KOOSs) were obtained. A Simulated Annealing optimization algorithm was used to identify medial and lateral laxity windows which maximized the 2-year KOOS pain score. Wilcoxon nonparametric tests were used to compare outcomes between groups.Significant associations were found between intraoperative joint laxity and 2-year KOOS pain outcomes throughout flexion. Clinically relevant laxity windows were defined medially and laterally in mid-flexion and flexion for improved outcomes, whereas only a lateral laxity window could be defined in extension. When all laxity windows were satisfied, a 14.5-KOOS point improvement was found (97.2 vs. 77.8, p = 0.0060) compared to knees which did not satisfy any window. Improvements in Activities of Daily Living (Δ8.8, p = 0.0143), Sports (Δ22.5, p = 0.0108), and Quality of Life (Δ18.7, p = 0.0011) KOOS subscores were also found in knees which satisfied all windows versus 0–1 window.Intraoperative joint laxity is associated with postoperative outcomes in a PS knee design, wherein patients balanced within identified laxity targets reported improved outcomes over those that did not. Clinically significant thresholds were defined and were predominately found in mid-flexion and flexion for medial and lateral laxity. When target windows were combined further improved outcomes were identified.
Keywords: total knee arthroplasty; joint laxity; posterior stabilized TKA; 2 years follow-up; KOOS; soft tissue balance